2020
DOI: 10.1001/jamainternmed.2020.2176
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Healthy Eating Patterns and Risk of Cardiovascular Disease

Abstract: The 2015-2020 Dietary Guidelines for Americans recommend multiple healthy eating patterns. However, few studies have examined the associations of adherence to different dietary patterns with long-term risk of cardiovascular disease (CVD).OBJECTIVE To examine the associations of dietary scores for 4 healthy eating patterns with risk of incident CVD. DESIGN, SETTING, AND PARTICIPANTSProspective cohort study of initially healthy women from the Nurses' Health Study (NHS) and the NHS II and men from the Health Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
163
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 274 publications
(201 citation statements)
references
References 40 publications
11
163
1
4
Order By: Relevance
“…The correlations between our healthful PDI and the Alternate Healthy Eating Index were 0•67 in the NHS and 0•68 in the NHSII. The correlations between our index and the Alternate Mediterranean Diet score were 0•37 in the NHS and 0•35 in the NHSII (47) . However, our plant-based diet indices are different from these other dietary indices in several aspects.…”
Section: Discussionmentioning
confidence: 70%
“…The correlations between our healthful PDI and the Alternate Healthy Eating Index were 0•67 in the NHS and 0•68 in the NHSII. The correlations between our index and the Alternate Mediterranean Diet score were 0•37 in the NHS and 0•35 in the NHSII (47) . However, our plant-based diet indices are different from these other dietary indices in several aspects.…”
Section: Discussionmentioning
confidence: 70%
“…Methods to confirm incident CVD have been published in detail elsewhere (Hart et al 2015b;Shan et al 2020;Yu et al 2016). Incident CVD was determined as the first occurrence of either fatal and nonfatal acute MI (ICD-9 code 410) or stroke (ICD-9 codes 430 to 437).…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…This is the case of the Mediterranean diet, traditionally rich in fiber from cereals such as whole-grain bread, pasta, couscous and other unrefined grains, and is rich in micronutrients and phytochemicals from fruit and vegetables of different colors and textures with many different potential health benefits [136][137][138]. Bioactive compounds like phenolic compounds, flavonoids, plant sterols, and carotenoids of plant origin are protective against chronic diseases, mainly thanks to their action upon lipid profile, endothelial function, and inflammatory mediators [139,140]. In particular, in vitro studies have amply demonstrated the beneficial effects on inflammation associated with the antioxidant activity of polyphenols, especially flavonoids such as flavonols, flavones, isoflavones, anthocyanidins, resveratrol, curcumin, tannins and lignans.…”
Section: Diet and Lifestylementioning
confidence: 99%